Advertising : an integrated marketing communication perspective - Belch, George E. [ (George Edward)] , 1951- (McGraw Hill, 2012)
This second edition builds on the success of the market-leading first edition, recognising that advertising has become a blank canvas, where marketers must look beyond traditional media and conventional thinking to achieve success